The degree of the practice of secondary school principals in Sakaka and Qaryat in KSA for organizational justice in their schools from the point of view of teacher - Rouili, Mohamed; Allab, Rachid (Finance and Business Economies Review, 2019)
This study aimed at finding out the degree of practicing organizational justice by the secondary school principals in skaka and alqurayat directorates from teachers' point of view. The study sample consisted of (309) teachers all the population of the study (343) teachers. To achieve the objectives of the study, the researcher developed the questionnaire of the practice of organizational justice, consisting of (28) items, and validity and reliability was established . The results showed that there were statistically significant differences at (≥ 0.05) according to gender and for females, The study showed that the degree of practicing the secondary school principals organizational justice in their schools from the point of view of the teachers was medium. And the results indicated that there were statistically significant differences (≥ 0.05) according to the experience variable for the category of experience (5- less than 10 years). The results also indicated that there were statistically significant differences at (≥ 0.05), which was in favor of BSc. Degree holders. The study recommended that secondary school principals exercise greater organizational justice with teachers and take into account the conditions of teachers with experience and higher academic qualifications.